Do Sovereign Defaults Hurt Exporters? - Eduardo Borensztein; Ugo Panizza (Inter-American Development Bank, Research Department, 2006)
This paper uses a difference-in-difference methodology similar to the one originally proposed by Rajan and Zingales (1998) to test whether defaulting hurts the more export-oriented industries. Strong support for this hypothesis was found, but contrary to the findings of previous studies, our estimations suggest that the effect of defaults is short-lived.
Keywords: 330; Internationale Staatsschulden; Außenhandelssektor; Schätzung; Welt